Outcomes of early social experiences on glucocorticoid and endocannabinoid systems in the prefrontal cortex of male and female adolescent rats - Rullo, Laura; Losapio, Loredana Maria; Morosini, Camilla; Mottarlini, Francesca; Schiavi, Sara; Buzzelli, Valeria; Ascone, Fabrizio; Ciccocioppo, Roberto; Fattore, Liana; Caffino, Lucia; Fumagalli, Fabio; Romualdi, Patrizia; et al. (Frontiers in Cellular Neuroscience, 2023)
Social and emotional experiences differently shape individual's neurodevelopment inducing substantial changes in neurobiological substrates and behavior, particularly when they occur early in life. In this scenario, the present study was aimed at (i) investigating the impact of early social environments on emotional reactivity of adolescent male and female rats and (ii) uncovering the underlying molecular features, focusing on the cortical endocannabinoid (eCB) and glucocorticoid systems. To this aim, we applied a protocol of environmental manipulation based on early postnatal socially enriched or impoverished conditions. Social enrichment was realized through communal nesting (CN). Conversely, an early social isolation (ESI) protocol was applied (post-natal days 14-21) This is a provisional file, not the final typeset article to mimic an adverse early social environment. The two forms of social manipulation resulted in specific behavioral and molecular outcomes in both male and female rat offspring. Despite the combination of CN and ESI did not affect emotional reactivity in both sexes, the molecular results reveal that the preventive exposure to CN differently altered mRNA and protein expression of the main components of the glucocorticoid and eCB systems in male and female rats. In particular, adolescent females exposed to the combination of CN and ESI showed increased corticosterone levels, unaltered genomic glucocorticoid receptor (GR), reduced cannabinoid receptor type-1 (CB1R) and fatty acid amide hydrolase (FAAH) protein levels, suggesting that the CN condition evokes different reorganization of these systems in males and females.